2013
DOI: 10.1080/17461391.2013.773090
|View full text |Cite
|
Sign up to set email alerts
|

Overuse in volleyball training/practice: A review on shoulder and spine-related injuries

Abstract: Overuse injuries are predominant in sports involving the repetition of similar movements patterns, such as in volleyball or beach volleyball, and they may represent as much a problem as do acute injuries. This review discusses the prevalence of two of the most common overuse-related injuries in volleyball: shoulder and back/spine injuries. Risk factors and the aetiology of these injuries are illustrated in order to make possible to initiate preventive programme or post-injuries solutions. Data collected from l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
1
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(77 citation statements)
references
References 68 publications
1
67
1
8
Order By: Relevance
“…However, the majority of the shoulder injuries are usually overuse injuries. They account for approximately 19% of all volleyball injuries (Seminati & Minetti, 2013) and result in the greatest time lost from training and competition (Verhagen et al, 2004). Repeated external rotation and elevation shoulder movements are common manoeuvres in volleyball and in other disciplines classified as 'overhead sports'.…”
Section: Introductionmentioning
confidence: 99%
“…However, the majority of the shoulder injuries are usually overuse injuries. They account for approximately 19% of all volleyball injuries (Seminati & Minetti, 2013) and result in the greatest time lost from training and competition (Verhagen et al, 2004). Repeated external rotation and elevation shoulder movements are common manoeuvres in volleyball and in other disciplines classified as 'overhead sports'.…”
Section: Introductionmentioning
confidence: 99%
“…The first one studied back injuries along with shoulder injuries as common pathologies in beach volleyball players (Seminati & Minetti, 2013). A year later, a study on the prevalence of disc degeneration prevalence and spondylolysis (Kulling et al, 2014) established that the most affected spinal levels were L4-5 in 14 (48%) and L5-S1 in 15 players (52%).…”
Section: Specific Injuriesmentioning
confidence: 99%
“…After deleting duplicates and applying the inclusion criteria to the titles and abstracts, 129 potentially relevant studies were included for the full text review. From those potentially relevant studies, 10 literature reviews were identified (Briner & Kacmar, 1997;Cools, Johansson, Borms, & Maenhout, 2015;Dugas, Chronister, Cain, & Andrews, 2014;Eerkes, 2012;Fong, Hong, Chan, Yung, & Chan, 2007;James, Kelly, & Beckman, 2014;Kox, Kuijer, Kerkhoffs, Maas, & FringsDresen, 2015;Magra, Caine, & Maffulli, 2007;Reeser, Verhagen, Briner, Askeland, & Bahr, 2006;Seminati & Minetti, 2013), while 90 studies were excluded for various reasons: mostly because these were not original studies or had an inappropriate study design, and data were not (solely) about volleyball. Since the reference check of the literature reviews and included studies did result in 5 additional relevant studies, 34 relevant original studies were included in our systematic review: 28 studies describe the incidence and/or prevalence of musculoskeletal injuries (Agel, Palmieri-Smith,der Beek, Bouter, & van Mechelen, 2005;Visnes, Hoksrud, Cook, & Bahr, 2005).…”
Section: Search Strategymentioning
confidence: 99%